2021
DOI: 10.1177/00221678211000621
|View full text |Cite
|
Sign up to set email alerts
|

Tales From the Dark Side: The Dark Tetrad of Personality, Supernatural, and Scientific Belief

Abstract: Theories such as the psychodynamic functions hypothesis, attribution theory, and the just world theory have been used to explain different types of supernatural belief. This study aims to examine “dark” personality traits and how they link to different beliefs using the Dark Tetrad. The Dark Tetrad” comprises narcissism, Machiavellianism, psychopathy, and sadism. Relationships have been found between dark personality traits and religious belief, but no studies have examined the Dark Triad or Tetrad and paranor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…Since collectivism represents a positive attitude towards being involved in a social group (as opposed to being a particular individual), the link between bullshit sensitivity and Machiavellian avoidance (as an attitude to believe that others have evil intentions, leading to a rejection of societal principles) is reasonable. In line with this, Schofield et al (2022) assumed that suspicious, distrustful aspects of Mach serve as protective factors against misinformation, and Ahadzadeh et al ( 2021) demonstrated the protective effect of scepticism against the endorsement of false beliefs. According to the latter authors, individuals with high scores in both Mach and scepticism are least likely to have false beliefs.…”
Section: Machiavellianism Supernatural Beliefs and Superstitionmentioning
confidence: 94%
See 2 more Smart Citations
“…Since collectivism represents a positive attitude towards being involved in a social group (as opposed to being a particular individual), the link between bullshit sensitivity and Machiavellian avoidance (as an attitude to believe that others have evil intentions, leading to a rejection of societal principles) is reasonable. In line with this, Schofield et al (2022) assumed that suspicious, distrustful aspects of Mach serve as protective factors against misinformation, and Ahadzadeh et al ( 2021) demonstrated the protective effect of scepticism against the endorsement of false beliefs. According to the latter authors, individuals with high scores in both Mach and scepticism are least likely to have false beliefs.…”
Section: Machiavellianism Supernatural Beliefs and Superstitionmentioning
confidence: 94%
“…In previous studies, Mach revealed positive relations with the endorsement of conspiracy beliefs, as well as supernatural phenomena and entities, such as psychokinesis, paranormal perceptions and religiosity (Ahadzadeh et al, 2021;Douglas & Sutton, 2011;March & Springer, 2019;Schofield et al, 2022). Like many of the other stated studies, Ahadzadeh et al ( 2021) treated Mach as a non-reflected, unidimensional trait that lacks evaluations of information as well as scepticism -an approach subject to a plethora of critique (Blötner & Bergold, 2022).…”
Section: Machiavellianism Supernatural Beliefs and Superstitionmentioning
confidence: 95%
See 1 more Smart Citation
“…The "belief in a just world" (Kaplan, 2012), for example, is rather sinister in nature and posits that "people get what they deserve." Perhaps it is unsurprising that adherents of this view often exhibit dark personality traits (Schofield et al, 2022). Many scientists also negatively regard paranormal beliefs, as demonstrated by four popular hypotheses for their endorsement and prevalence, namely: (1) Social marginality (i.e., believers tend to be lower socioeconomic class, female, or a particular race: Emmons & Sobal, 1981); (2) Cognitive deficits (i.e., believers show poor critical thinking and rely too heavily on intuition: Dean et al, 2022); (3) Psychodynamic functions (i.e., believers are potentially mentally ill or have a set of certain (usually negative) personality traits); and (4) the Worldview model (i.e., paranormal believers endorse other similar beliefs, such as religious or other esoteric spiritual type beliefs: Zusne & Jones, 1982).…”
Section: Focus Area A: Drivers Of Darker Religio-spiritual Beliefs Or...mentioning
confidence: 99%
“…The above theories suggest that the factors that relate to people's belief-formation are cognition and personality, but there is considerable debate about the nature of this relationship (Schofield et al, 2020). Positive types of personality usually correlate with religious beliefs, and negative types with paranormal beliefs, although there are exceptions to these trends, and the overall effect of personality is very small (Schofield et al, 2022). A key trait in this context is schizotypy (Schofield et al, 2020), which is related to magical ideation and represents a latent personality construct or liability to develop schizophrenia (Claridge, 1997;Lenzenweger, 2010).…”
Section: Focus Area A: Drivers Of Darker Religio-spiritual Beliefs Or...mentioning
confidence: 99%